(3JMaI Phi GdCdHGH ajef Mce OeTb ef GdNdaGA hGdedhc hGdfhGHs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdbOje GdOGFe ebOQ GdehJ Ydi GHf BOe s
(3BNQgG (B:s
(3jfJgi gPG GdTQM HCNHGQ GdCejQ YdGA GdOjf hONhdg HOeTb SfI (B760(3g` s
(3CQLhRI eY TQMgGs
(3GdfSNI eUhQI Yf GdCUd GdeMahX HGdecJHI GdCgdjI HHGQjSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B32 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B35 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs